Hubungan Pemberian ASI Eksklusif dan Lingkar Kepala dengan Perkembangan Motorik Bayi Usia 6-12 Bulan di Surakarta - SIWI HESTI UTAMI; BUDIYANTI WIBOWORINI; ETI PONCORINI PAMUNGKASARI (Faculty of Medicine Universitas Sebelas Maret, 2018)
Introduction: Motor development needs to be considered to detect the presence or absence of delays in infant’s development which can affect their potency in the future. Exclusive breastfeeding contains lactose, taurine, DHA, and AA which are needed for motor development. Head circumference is related to brain development as one of motor control organs. This study aimed to analyze the relationship between exclusive breastfeeding and head circumference with motor development of infants aged 6-12 months in Surakarta. Methods: This was an analytical observational study with a cross sectional design. The subject were infants aged 6-12 months in Puskesmas Gajahan and Puskesmas Ngoresan Surakarta who met the inclusion criteria. Data obtained from interviews, measurements of head circumference, and assessments of motor development, in 84 subjects that selected purposely. The data were analyzed using Chi Square test, Odds Ratio (OR), and logistic regression.Results: There was a significant relationship between exclusive breastfeeding and motor development (p<0,001; OR=9,88) but no significant relationship was found between head circumference and motor development (p=0,208; OR=5,35), complementary feeding and motor development (p=0,242; OR=0,52), sex and motor development (p=0,400; OR=1,59), age and motor development (p=0,432; OR=0,65). Conclusion: Infants aged 6-12 months who are exclusive breastfed and had normal head circumference have greater chances to experience motor development that is age – appropriate.